The Development of Learning Model With An-Nafs Learning Theory - Rivauzi, Ahmad (Institut Agama Islam Negeri Imam Bonjol Padang, 2018)
This article aims to explore the theory, An-Nafs learning model and the response of religious teachers at elementary schools in Palupuh, Agam. This study involved all the religious teachers from 19 schools in Palupuh. Based on the questionnaire distributed and then processed by using Likert scale, obtained excellent response from them, both on the aspects of theoretical understanding, urgency, and the benefits of its application to the learning of Islam. The finding showed that all the learning theories today can not be separated from the philosophical view of the nature of man and God. This view will determine how a person treats humans, educates and learns them and also the purpose of the education and learning. The essence of learning in the theory and model of learning An Nafs is the occurrence of changes in the An-Nafs itself as the potential human-psychological (jasad-ruhani)